Load-deformation characteristics of acellular human scalp: assessing tissue grafts from a material testing perspective - Zwirner, Johann (Sci Rep, 2020)
Acellular matrices seem promising scaffold materials for soft tissue regeneration. Biomechanical properties of such scaffolds were shown to be closely linked to tissue regeneration and cellular ingrowth. This given study investigated uniaxial load-deformation properties of 34 human acellular scalp samples and compared these to age-matched native tissues as well as acellular dura mater and acellular temporal muscle fascia. As previously observed for human acellular dura mater and temporal muscle fascia, elastic modulus (p = 0.13) and ultimate tensile strength (p = 0.80) of human scalp samples were unaffected by the cell removal. Acellular scalp samples showed a higher strain at maximum force compared to native counterparts (p = 0.02). The direct comparison of acellular scalp to acellular dura mater and temporal muscle fascia revealed a higher elasticity (p < 0.01) and strain at maximum force (p = 0.02), but similar ultimate tensile strength (p = 0.47). Elastic modulus and ultimate tensile strength of acellular scalp decreased with increasing post-mortem interval. The elongation behavior formed the main biomechanical difference between native and acellular human scalp samples with elastic modulus and ultimate tensile strength being similar when comparing the two.